The lichens of forest rocky communities of the hill Muroigora (Arkhangelsk Region, Northwest Russia) - Tarasova, Viktoria N.; Sonina, Angella V.; Androsova, Vera I.; Stepanchikova, Irina S. (Folia Cryptogamica Estonica, 2016)
The present study reports 188 species and 2 subspecies of lichens and allied fungi from forest rocky communities of the hill Muroigora situated in the Arkhangelsk part of the National park “Vodlozersky” (Arkhangelsk Region, NW Russia). Lepraria ecorticata is new to Russia, and 13 more species are new for the mainland area of the Arkhangelsk Region: Arthonia mediella, Arthonia vinosa, Bacidia igniarii, Bryoria vrangiana, Chaenothecopsis pusiola, Cladonia caespiticia, Lecidea plana, Lepraria borealis, Micarea misella, Pertusaria pustulata, Schaereria cinereorufa, Xanthoparmelia pulla and Xylographa trunciseda. Two lichen species, Bryoria fremontii and Lobaria pulmonaria, are in the Red Data Books of the Arkhangelsk Region and Russian Federation. A total of 89 species are reported as new for the Vodlozersky National Park.